A Brief Look on Balinese Language Maintenance and Shift in Denpasar - Darmasetiyawan, I Made Sena (Lingual Journal of Language and Culture; Vol 14 No 2 (2022): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2022.v14.i02.p08, 2022)
Balinese language were spoken by Balinese that generally are multilingual speakers, since they would also need to be proficient in Indonesian and sometimes even have a good command of English; particularly those living in tourism area. Between Indonesian and English, the position of Balinese language in regard to the language maintenance and language shift can become a quite complex matter depending on the context and matter in conversation. This study tried to provide brief example of findings that indicated several factors that can insinuate the shift in language and the effort towards maintaining Balinese language. Keywords: multilingual, language maintenance, language shift, context